Águas espessas : Hilda Hilst e a imagem poética - Santos, César de Oliveira (2016)
The image of Water seems to be a major component among the elements that compose the Cantares de perda e predileção [Songs of loss and predilection] (1983), by Hilda Hilst. Whether as a central component of the poem metaphor or a splash of discreet presence, the Water element makes the book a wealth of meanings. We extract from this book for analysis the treatments granted to Desire and Time. In the first case, we see an opaque water, gleaming anguish and loneliness in a song that is predestined to stop its search in the case of a successfully accomplishment. Although the specificity of each poem, the Water element receives nuances of vertigo common to individuals focused on water, as stated by Bachelard (1942). In the second case, we have a stream doomed to finitude, a condition that is one of the reasons for the thickness of Desire. Some songs show the despair of being-toward-death of Heidegger (1927), according to whom only the (potentially eternal) temporality of poetry seems to save, as says Alfredo Bosi (1977) commenting on the intersection of times (of the poetry and ours). At the confluence of these two analytic matrices - Desire and Temporality - we demonstrate how the plasticity promoted by the Water image recurrence favors the production of emotions in the reader, since, according to Octavio Paz (1956), Image is responsible both for recreating real contradictions and for destabilizing the alleged structural rationalism of our daily lives. For this, we especially use the concepts of perception and look of Merleau-Ponty (1960) and Georges Didi-Huberman (1992), respectively, to demonstrate how, in the act of reading, Language enables our perception to remain on the text and at the same time is changed by it, making completely unattainable to critical discourse the inexplicable subjectivity inherent to the aesthetic experience.